The Synergy Of Islamic Banking And Village-Owned Enterprises (BUMDes) To Strengthen Unbankable Business Capital - Nurnasrina, Nurnasrina; Putra, Popi Adiyes; Khairunisa, Madona; Lubis, Haniah; Jenita, Jenita (MUI Kota Pekanbaru, 2023)
This study aims to determine the synergy that can be implemented between Islamic Bank and Village Owned Enterprises (BUMDes) to strengthen unbankable business capital and to assess the application of sharia contracts toward some products provided by BUMDes. The research methodology used qualitative analysis, primary data obtained from informants, namely one branch manager of Islamic Bank of Indonesian (BSI), Pekanbaru branch and 14 BUMDes leaders in Tambang District, Kampar. The results show that first: two forms of synergy can be implemented between BSI and BUMDes to strengthen unbankable business capital, namely BSI finances through BUMDes then distributed to the unbankable micro-entrepreneurs and BSI distributes directly to the unbankable micro-entrepreneurs based on BUMDes recommendation then BSI provides a fee after BUMDes gives the guarantee, second: the application of sharia contracts toward some products supplied by BUMDes currently could use wadi`ah, mudharobah, musyarokah, murobahah, salam, istisna, ijaroh and wakalah.